Prediction of final settlements of buildings constructed on expansive soils - Pérez-Rea, MarÃa-de-la-Luz; Ayala, Tania; Castano, Victor (International Journal of Engineering and Technology, 2015)
Because the action of the swelling pressure, the settlements caused by the transmitted load from the structure on expansive soils, and the settlements calculated by classic theories of soils mechanics are different. This swelling pressure acts in opposite direction to the weight of the building. In this paper, the authors propose the use of a volumetric strain coefficient by settlements exp, in a soil-structure interaction algorithm taking into account the expansive soil behavior in the reduction of the settlement magnitude when a building is placed above soil. It’s necessary to know the initial properties of the expansive unsaturated soil and the load building conditions. A laboratory process is described for determining the aexpcoefficient.